ANALISIS KEBUTUHAN RAK PENYIMPANAN REKAM MEDIS AKTIF PASIEN RAWAT INAP DI RUMAH SAKIT UMUM PINDAD BANDUNG - Vera Dwi Astuti; Silviani (INFOKES (Informasi Kesehatan), 2020)
This research aims to determine the need for inpatiens active medical record storage shelf at Rumah Sakit Umum Pindad Bandung. The research method used is qualitative method with descriptive and technical approaches. Data collection was carried out by direct observation in the field, conducting interviews and literature studies related to the subject matter. The sampling technique used Simple Random Sampling. From the research results, medical records storage shelf needs hospitalization active for years 2020 to 2024 based on calculations using the least squares method (least square) as many as 28 storage shelf, RSU Pindad Bandung has 18 storage shelf so that should add 10 storage shelf,with problems that arise, among others: (1) the lack of inpatients active medical record storage shelf so that there are medical records stored in container boxes and on top of the outpatient medical record storage shelf (2) In the company budget work plan year 2020 has proposed additional storage shelf but during this time of the pandemic items to unrelated covid-19 were postponed. As for the suggestions given to fix these problems are(1) based on the calculations that the author has done, the author suggests adding 10 shelf for storage of active inpatiens medical records for years 2020 to 2024 (2) immediately realizing the need for shelf so that medical records are not in keep it outside the storage shelf and the medical records look neat and keep the medical records confidential.